Research on the Application of Environmental Art Design Based on the Combination of VR and Panoramic Video Technology - Yingqi Kong (Hindawi Limited, 2021)
The panoramic video technology is introduced to collect multiangle data of design objects, draw a 3D spatial model with the collected data, solve the first-order differential equation for the 3D spatial model, obtain the spatial positioning extremes of the object scales, and realize the alignment and fusion of panoramic video images according to the positioning extremes above and below the scale space. Then, the panoramic video is generated and displayed by computer processing so that the tourist can watch the scene with virtual information added to the panoramic video by wearing the display device elsewhere. It solves the technical difficulties of the high complexity of the algorithm in the system of panoramic video stitching and the existence of stitching cracks and the “GHOST” phenomenon in the stitched video, as well as the technical difficulties that the 3D registration is easily affected by the time-consuming environment and target tracking detection algorithm. The simulation results show that the panoramic video stitching method performs well in real time and effectively suppresses stitching cracks and the “GHOST” phenomenon, and the augmented reality 3D registration method performs well for the local enhancement of the panoramic video.